In vitro regeneration of pumpkin (cucurbita maxima) through shoot apical meristem - Haque, ME; Rezwana, D; Islam, MA; Sikdar, B (Journal of Bio-Science, 2011)
Context: Pumpkin (Cucurbita maxima) is very important vegetable crop. It is damaged by several types of diseases, especially viral diseases which reduce the total yield of pumpkin. This is very difficult problem and such type of problem can be overcome by meristem culture. Objectives: To develop suitable protocols for indirect regeneration of pumpkin plant through shoot apical meristem. Materials and Methods: Meristems were isolated from 15-21 days in vivo grown plants by collecting shoot tips and were prepared (0.2-0.5 mm) under 4X zoom stereo-microscope remaining two leaves primordia. Inoculation of explants was made singly per culture vessel in semisolid MS fortified with different concentrations and combinations of cytokinin and auxin. Results: Among different concentrations, 1.0 mg/l BAP showed best response for callus induction. Calli were sub cultured for shoot formation in MS containing BAP singly or combination with GA3 and 1.5 mg/l BAP + 0.1 mg/l GA3 gave better result. In vitro regenerated shoots were rooted well in ½ strength MS with 0.5 mg/l IBA and micro plants were acclimatized successfully in natural condition. Conclusion: Indirect regeneration of pumpkin plants through shoot apical meristem has been established. Keywords: Growth regulators; in vitro regeneration; Pumpkin; Cucurbita maxima. DOI: http://dx.doi.org/10.3329/jbs.v18i0.8784 JBS 2010; 18(0): 104-107